Short- and long-term effects of a maternal low-protein diet on ventilation, O2/CO2 chemoreception and arterial blood pressure in male rat offspring. Issue 4 (23rd September 2013) - de Brito Alves, José Luiz; Nogueira, Viviane Oliveira; de Oliveira, Gerliny Bezerra; da Silva, Glauber Santos Ferreira; Wanderley, Almir Gonçalves; Leandro, Carol Góis; Costa-Silva, João Henrique
Abstract : Maternal undernutrition increases the risk of adult arterial hypertension. The present study investigated the short- and long-term effects of a maternal low-protein diet on respiratory rhythm, O2 /CO2 chemosensitivity and arterial blood pressure (ABP) of the offspring. Male Wistar rats were divided into two groups according to their mothers' diets during gestation and lactation: control (NP, 17 % of casein) and low-protein (LP, 8 % of casein) groups. Direct measurements of ABP, respiratory frequency (RF), tidal volume ( V T ) and ventilation (VE), as well as hypercapnia (7 % CO2 ) and hypoxia (7 % O2 ) evoked respiratory responses were recorded from the awake male offspring at the 30th and 90th days of life. Blood samples were collected for the analyses of protein, creatinine and urea concentrations. The LP offspring had impaired body weight and length throughout the experiment. At 30 d of age, the LP rats showed a reduction in the concentrations of total serum protein (approximately 24 %). ABP in the LP rats was similar to that in the NP rats at 30 d of age, but it was 20 % higher at 90 d of age. With respect to ventilatory parameters, the LP rats showed enhanced RF (approximately 34 %) and VE (approximately 34 %) at 30 d of age, which was associated with increased ventilatory responses to hypercapnia (approximately 21 % in VE) and hypoxia (approximately 82 % in VE). At 90 d of age, the VE values and CO2 /O2 chemosensitivity of the LP rats were restored to the control range, but the RF values remained elevated. The present data show that a perinatal LP diet alters respiratory rhythm and O2 /CO2 chemosensitivity at early ages, which may be a predisposing factor for increased ABP at adulthood.